(untitled) (International Seven Journal of Health Research, 2023)
Due to recent demographic and epidemiological changes in the population, marked by progressive and accelerated ageing followed by chronic-degenerative diseases, long-term care has become necessary and, with it, the need for lasting contact with medical professionals. All this contact takes place through communication. Communication is a social practice that comes from an interaction between individuals, and can be expressed verbally, through speech; and non-verbal aspects, writing, behavior, gestures, touch, among others. In the context of care, it is understood that communication must have an effective and therapeutic effect. This is because, when communication is carried out effectively, it allows patients and their families to have a greater understanding, as well as acquiring ways of coping with the problem, realizing their role as being an active subject throughout care. In view of the facts presented, the general aim of this study was to investigate the doctor-patient communication process through the literature. For this article, the integrative literature review methodology was used, carried out through data collection in databases between July and August 2023. The inclusion criteria were articles published between 2015 and 2022, articles in Portuguese and English, articles acquired in full and free of charge, which addressed the topic of doctor-patient communication. To develop the results of this article, 10 articles relevant to the topic were added to the descriptors. The results show the enormous importance of both verbal and non-verbal communication in building doctor-patient interpersonal relationships. Even before a dialogue is established, the relationship is developed through facial expressions, behavior and gestures. Thus, in the doctor-patient relationship, it is important that contact is developed in trust and transparency. It can be concluded that the studies investigated in this review converge in terms of the complexity of the issue, and that health professionals need to be better prepared, as well as developing interventions with patients and their families to develop communication skills. Regardless of whether the communication is verbal or non-verbal, it is important for the doctor to master and establish ways of interacting with the patient.